An electrically driven omnidirectional self-leveling tracked chassis with event-triggered sliding-mode control for hilly orchard operations - Yueguang Liu; Jianxi Zhu; Bohua Zhao; Zhiguo Li; Likui Feng; Yuanyuan Zhang; Chonglei Sun; Tuo Pi; Zhenbo Wei (Computers and Electronics in Agriculture, 2026)

Bridging structure and performance in ZnIn2S4 photocatalysts: Mitigating photocorrosion and recombination toward sustainable environmental applications - Zhuolin Cai; Yuanhang Pi; Jun Hu; Hongbo Huang; Ye Liu; Feipeng Jiao (Environmental Research, 2026)

Zygote electroporation of base editor ribonucleoproteins enables efficient single-target editing but reveals limitations of multiplex base editing in sheep - Mengting Cheng; Yun Wang; Haoran Xu; Muhammad Faheem Qurashi; Xinrong Li; Xueyi Ding; Jun Liu; Wenhui Pi; Chunhe Xiang (Theriogenology, 2026)

Exploring the effect of micro-pressure stewing technology on the formation of key aroma compounds in pork by means of lipidomics and lipid-derived free radical analysis - Huan Liu; Shuqi Zhao; Guofeng Jin; Pi Li; Jianjun Li; Peng Gao; Jiangtao Xing; Jianmei Zhang; Ye Zhang; Weiting Wang; Pengfei Du; Chengyu Zeng; et al. (Food Research International, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Soil aggregate fractionation modulates Mollisol organic carbon biomineralization and CO2 emission during freeze-thaw cycles - Wenjuan Zou; Kunfu Pi; Hongyan Li; Qianyong Liang; Lifen Liu; Fereidoun Rezanezhad (Applied Geochemistry, 2026)

Integration of Deep Learning with Geographical Discrepancy Analysis for IMERG Precipitation Fusion: Application to Flash Flood Simulation - Xing Liu; Yang Guo; Zhengguo Pi; Kun Chen; Jidong Li; Weibin Huang (Water Resources Management, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A single-cell perspective on polyethylene microplastic toxicity: linking fibroblast reprogramming to immune microenvironment alterations in the lung - Xiaoxuan Fan; Jingtian Liu; Shumin Huang; Xu Wang; Tianming Liu; Xiaochen Ma; Jiayi Zhou; Pi Guo; Yinge Wu (Journal of Hazardous Materials, 2026)

Prior-guided multi-domain mixture-of-experts for multimodal Earth observation data gaps - Chuang Liu; Jianhua Guo; Yingdong Pi; Xiao Wu; Zhiqi Zhang; Ru Chen; Xinyi Wang; Mi Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Hydrogeochemical constraints on the genesis, fluid mixing, and heavy metal mobilization of low-temperature geothermal systems in the Mufushan granite batholith, South China - Linxin Li; Zhengqing Wu; Lei Wang; Jian Ou; Jing Pi; Sheng Liu; Lala Wei; Liuqin Huang; Hongchen Jiang; Yanlong Dong (Geothermics, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Analysis and identification of geographical indication protected Huangjiu based on multimodal data combined with chemometric methods - Xiaodan Liu; Qiuwen Shan; Xianhao Ding; Chao Ji; Yonghui Yu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Food Control, 2026)

Climatic drivers of vector-borne diseases: A nationwide causal inference study in China - Xu Wang; Jiayi Zhou; Jingtian Liu; Ying Liang; Fei Lu; Linjing Zhang; Yunchong Yao; Xinyue Fang; Yangchun Zheng; Xiaobo Liu; Zhong Hu; Qingying Zhang; et al. (Environmental Research, 2026)

Integrative genomic analyses reveal genetic structuring and cyto-nuclear incongruences within the Corbicula species complex in China - Yangxin Tang; Linwei Liu; Jie Pi; Xinhua Liu; Jianguo Xiang; Joong-Ki Park; Neil E. Coughlan; Deliang Li (Molecular Phylogenetics and Evolution, 2026)

Atomically dispersed Ruδ+-Ov-Ce3+ interfaces enable photothermal synergy-driven dry reforming of methane via a CH3O⁎ intermediate-mediated pathway - Fei Wang; Shule Liu; Jianfeng Lu; Jing Ding; Jing Xiao; Yunhong Pi; Weilong Wang (Chemical Engineering Journal, 2026)

Triggering mechanisms of the 2024 M4.5 earthquake swarm in Mozhugongka, Tibetan Plateau: Constraints from seismotectonics and the role of deep fluids - Guoqiang Ji; Xingzhong Du; Yong Li; Xuan Ke; Xiaohui Hu; Huabiao Liu; Yu Tang; Kairong Pi (Journal of Seismology, 2026)

Flow-assembled Janus catalyst arrays for low-energy-barrier cascade dechlorination and mineralization of chlorinated organic compounds in water - Delai Zhong; Haonan Zhang; Beizhao Chen; Yuchen Wu; Pi-Jun Duan; Mingjie Huang; Yue Zhi; Caihong Liu; Nan Wang; Yi Jiang (Journal of Hazardous Materials, 2026)

Novel mechanism of enhancing Arthrospira chlorophyll photostability by natural deep eutectic solvent: Axial coordination between betaine-xylitol and the porphyrin ring - Shuyu Wang; Tianxiang Pi; Yixiao Liu; Yangbin Wang; Fangwei Li; Mingyong Zeng (Bioresource Technology, 2026)

Diversity of arbuscular mycorrhizal fungi of Taiwan cypress along altitude in tropical forests - Wan-Rou Lin; Hsuan-Min Cheng; Ren-Cheng Liu; Tzu-Chao Lin; Lei-Chen Lin; Pi-Han Wang (Tropical Ecology, 2026)

FGF19 promotes cartilage destruction in the progress of temporomandibular joint osteoarthritis - Haoran Chen; Yujia Cui; Yi Liu; Caixia Pi; Jianing Wu; Jianxun Sun; Xian Liu; Tao Zuo; Jing Xie (Cell and Tissue Research, 2026)

LSSCM-MobileTeaNet: A UAV-based lightweight spatial–spectral convolution model for large-scale estimation of chlorophyll and nitrogen content in tea plantations - Guoquan Pei; Defu Liu; Hongyuan Shi; Zhengzhao Pi; Xueying Qian; Bing Zhou; Baijuan Wang; Wendou Wu (Computers and Electronics in Agriculture, 2026)

Single-nucleotide editing of a strigolactone receptor confers virus resistance in rice - Qinglin Pi; Yule Liu (Molecular Plant, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

Experimental and multiscale study on the mechanism of SO3 removal in pectin-modified chemical agglomeration - Lei Zhou; Manyun Xu; Huyuan Lu; Yiren Pi; Fengbin Ji; Zhe Liu; Zhiling Wang; Heng Chen (Chemical Engineering Journal, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Soft sensing of NOx emissions in municipal solid waste incineration using a CBAM–CNN–Transformer model - Wenjing Li; Zhenghui Li; Anli Zhou; Wen Liu; Jianghong Chen; Wenbo Pi; Zhimin Lu; Shunchun Yao (Waste Disposal & Sustainable Energy, 2026)

Optimizing an anaerobic/aerobic/anoxic process by intermittent aeration and magnetic-activated-carbon-assisted aerobic sludge granulation for improved nitrogen and phosphorus removal - Yunsong Fang; Wenjie Liu; Kun Xin; Liu Pi; Zhenbao Wang; Likun Zhao; Hua Zhu; Yanjuan Lu; Jinyu Chen; Xuhui Mao (Journal of Water Process Engineering, 2026)

The interaction between vegetation greenness and hydro-climatic factors in China - Yuyue Xu; Jiangling Liao; Qing Liu; Yuchen Li; Junzheng Pi; Chang-Qing Ke; Jianli Chen; Hang Pan; Lixin Wang; Liyin He; Ling Yao; Chenghu Zhou (Journal of Hydrology, 2026)

A non-destructive workflow integrating X-ray computed tomography and machine learning for multi-defect identification and kernel plumpness assessment of in-shell walnuts - Menglong Ma; Ming Zhang; Haitao Fu; Yixiao Wang; Ning Yang; Huang Dai; Fuwei Pi; Xiaodan Liu; Jiahua Wang (Food Control, 2026)

Boosting the built-in electric field via sulfur vacancy engineering in an g-C3N4@FeS2 Z-scheme heterojunction for TC photocatalytic degradation: Process, mechanism and application - Yue Zhou; Xianbin Hu; Fangfang Zhao; Yiren Pi; Xiaoming Peng; Zhen Huang; Xing Xu; Peng Zhan; Caihua Liu; Junhui Zhou (Chemical Engineering Journal, 2026)

The epigenetic and epitranscriptomic regulation of Brd4-Mettl3 axis on STING mediated vascular calcification - Junyong Zhao; Xiaolin Luo; Zelan Wang; Wenjian Luo; Shaofa Wu; Xingyu Ma; He Liu; Yang Chen; Shixian Pi; Jiawen Zhang; Jihang Zhang; Chuan Liu; et al. (Inflammation Research, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Comparison of long-term and short-term immunogenicity based on two different types of tuberculosis subunit vaccines - Mingming Zhou; Lifa Xu; Xiaochun Wang; Zian Zhang; Yun Xu; Qiangsen Zhong; Runlin Wang; Guoduo Liu; Jiagao Wu; Zixiao Wang; Sian Liu; Yuntao Yang; et al. (Archives of Microbiology, 2026)

N/O bi-vacancy Z-type heterostructure MoOx/g-C3N4 modified copper foam for photo-enhanced electrocatalytic reduction of As(III) to As(0) in strongly acidic wastewater - Minhan Pi; Xin Gao; Ning Liu; Shaofeng Wang; Xiangfeng Zeng; Yongfeng Jia (Chemical Engineering Journal, 2026)

Linking joint exposures to indoor and outdoor air pollution and residential greenness with male sperm quality: Based on human sperm banks from two provinces in China - Tingting Dai; Yunchong Yao; Xiaorong Li; Ruinian Zheng; Jiayi Zhou; Xu Wang; Jingtian Liu; Roumei Cai; Deshun Huang; Chunying Song; Tianqing Meng; Pi Guo (Journal of Hazardous Materials, 2026)

Unveiling the gut-brain axis: How chronic exposure to arsenic-induced microglial pyroptosis drives Alzheimer's disease-like pathology - Jianyu Qu; Xin Jiang; Ying Ma; Xin Sheng; Changyi Pi; Yuanbin Wang; Qiurong Xu; Rican Li; Peiran Wang; Dongping Qian; Ji Wang; Zili Yi; et al. (Journal of Hazardous Materials, 2026)

Cadmium Exposure Facilitates Oral Squamous Cell Carcinoma Progression and Epithelial–mesenchymal Transition Through the Upregulation of ATP1B4 - Jianbo Zhang; Jingdian Li; Jinghong Liu; Yongchun Peng; Huifeng Pi; Weijia Qing; Zhijing He; Xi Zhou; Bo Li; Junxin Liu; Qingyun Lin; Tengfei Fan (Biological Trace Element Research, 2026)

Glacial changes in the eastern Kunlun Mountains since the Little Ice Age - Sai Lin; Jinhua Liu; Yingkui Li; Haiping Hu; Changsheng Ye; Qiang Liu; Shunzi Pi (Quaternary International, 2026)

Simultaneous non-destructive detection of watercore and bruising in ‘Fuji’ apples via X-Ray computed tomography: Dual-threshold segmentation and machine learning classification - Haitao Fu; Menglong Ma; Yixiao Wang; Ziwei Wang; Jun Wang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Postharvest Biology and Technology, 2026)

Investigating the land hermit crab trade in physical pet shops across three Asian Countries: Implications for conservation management - Chia-Hsuan Hsu; Shi-Sheng Liu; Sin-Tung Choi; Tzu-Pi Chen; Bao-Min Gan; Wei-Ting Chen; Takahiro Kubo (Journal for Nature Conservation, 2026)

Maternal exposure to indoor and outdoor air pollution during pregnancy increases offspring risk of autism spectrum disorder - Lingxi Wang; Wei Li; Yunchong Yao; Xiufang Jiang; Dongmei Ma; Yinxia Liu; Yunhua Deng; Lijiao Sun; Hong Li; Yuping Zhao; Guangyang Peng; Guo Wei; et al. (Environmental Research, 2026)

The application of magnetic therapy in stroke treatment: Traditional treatment and biomaterials - Yi Fan; Xinyu Zhang; Lei Zhang; Xiaoyu Han; Haitong Zhao; YuJie Zhong; Xuan Jiang; Yutian Wei; Yan Pi; Yunyan Wang; Xinyi Yao; Yuge Ye; et al. (Chemical Engineering Journal, 2026)

Natural organic matter drives iodine biogeochemical cycling in multi-layered redox dynamic groundwater systems - Xingtao Liu; Xianjun Xie; Junxia Li; Yanlong Li; Kun Qian; Kunfu Pi; Yanxin Wang (Journal of Hydrology, 2025)

CYP450 activation and mitophagy induction mediate Ti3C2 MXene detoxification in RAW 264.7 cells - Yujiao Liu; Xuan Mao; Yongyi Wei; Xiaodi Li; Jianbo Jia; Qingmeng Liu; Jian Liu; Yu Wang; Xiaofei Zhou; Huihui Wang; Jingbo Pi; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Unique ectomycorrhizal fungal association is a major conservation dilemma for the threatened ectomycorrhizal tree species - Ren-Cheng Liu; Wan-Rou Lin; Alija Bajro Mujic; Pi-Han Wang (Journal for Nature Conservation, 2025)

New insight into the formation mechanism of key aroma compounds in the micro-pressure stewed duck meat: A volatilomics and lipidomics-based approach - Lei Zhao; Lin Li; Pi Li; Peng Gao; Jiangtao Xing; Chengyu Zeng; Cheng Li; Wanmei Wu; Daohong Zhang; Huan Liu (Food Research International, 2025)

Characterization of volatile compounds in roasted plant-based patties packaged with different disposable lunchboxes - Jingyu Li; Xinhe Zhang; Wenjing Li; Chanchan Sun; Pi Li; Shuqi Zhao; Hengheng Wang; Xiangru Wei; Matta Ebaid; Daohong Zhang; Lei Zhao; Huan Liu (Food Research International, 2025)

Strategy comparison for purifying phycocyanin from microplastic-contaminated Spirulina platensis: A dual evaluation of product quality and microplastic removal - Zhiheng Yue; Yixiao Wang; Yuhang Zhao; Huang Dai; Xiaodan Liu; Fuwei Pi; Xin Liu; Jiahua Wang (Food Chemistry, 2025)

Synergistic bulk-interface modification enables exceptional electrochemical performance of high-voltage LiNi0.5Mn1.5O4 cathode - Pei Wang; Yusong Ding; Hancheng Ma; Pu Cai; Zibing Pi; Ruixi Chen; Wei Chen; Qian Liu; Wen Luo (Chemical Engineering Journal, 2025)

Synergistic and continuous driving of Fe(III)/Fe(II) cycle by electron-rich organic contaminants and peroxymonosulfate: Homogeneous feasibility and heterogeneous application - Jin Chai; Yu Wei; Haoran Kong; Hui Liu; Zhuohan Li; Junshuo Huang; Ruobing Pi; Zhe Yang; Xuhui Sun (Chemical Engineering Journal, 2025)

Chelation-assisted ion exchange of MOR zeolite for enhancing CO2 capture under humid condition - Zhipeng Qie; Minghui Hu; Wenqi He; Yao Zhang; Zhongbao Liu; Huaizhong Xiang; Zepeng Wang; Dafeng Yang; Shuyi Yao; Xinxin Pi; Hongxing Dai (Chemical Engineering Journal, 2025)

Investigation of Cavitation Flow Field and Flow Loss in Shaftless Water-Jet Propulsion Pump Under Different Acceleration Conditions - Jianing Lei; Yong Wang; Houlin Liu; Ming Li; Qing Pi (Journal of Marine Science and Engineering, 2025)
This study discusses the effect of different acceleration modes on the shaftless water-jet propulsion pump’s operational performance. Following the usage of Renault-time-mean Navier–Stokes (N-S) equations combined with an application of the shear stress transport (SST) k-ω turbulence mode and reinforced by an experimental test platform, the research explores internal energy loss shaftless water-jet propulsion pump flow behavior under exponential and linear acceleration processes. The results indicate that, compared to linear acceleration, the cavity volume within the impeller is marginally greater during the initial phase of exponential acceleration; however, this trend reverses in the subsequent stages; The amplitude of fluctuations in the pressure pulsation coefficient at both the mid-span and root regions of the blade, along with the amplitude corresponding to the primary frequency of the pressure pulsation, are comparatively reduced. Turbulent entropy production at the rim constitutes a significant component of energy loss; however, the total entropy production exceeds this contribution.

Manganese oxides for electrochemical adsorption of metal ions in aqueous environments: A comprehensive review from fundamentals to applications - Xiong Yang; Jiahai Yu; Yafei Shi; Kewu Pi; Chengshuai Liu; Guohong Qiu (Critical Reviews in Environmental Science and Technology, 2025)

Development of a neuroendocrine factor-modified scaffold with superior osteogenic, vasculogenic, and anti-inflammatory properties - Zhilong Pi; Zexing Chen; Tao Liu; Ying Zhang; Xiangling Ye; Xiangyang Ma (Chemical Engineering Journal, 2025)

Biosynthesis of bicyclo[3.3.1]nonane derivatives in Hypericum sampsonii - Lukas Ernst; Hui Lyu; Pi Liu; Christian Paetz; Hesham MB Sayed; Tomke Meents; Hongwu Ma; Ludger Beerhues; Islam El-Awaad; Benye Liu (Phytochemistry Letters, 2025)

Water-first, energy-second: Water management strategies propelling solar-driven interfacial water evaporation beyond limits - Changyuan Song; Wenjing Pi; Penglai Li; Wentao Liu (Journal of Environmental Chemical Engineering, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Nondestructive classification of internal defects in camellia seeds and chestnuts using X-ray imaging: optimization and comparison of deep learning classifiers - Menglong Ma; Haitao Fu; Yixiao Wang; Zelin Lu; Ziwei Wang; Jingjing Cheng; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Control, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

A size-stable konjac-based hydrogel solar evaporator for efficient seawater desalination based on the Hofmeister effect - Changyuan Song; Xuyang Li; Wenjing Pi; Weihua Zhang; Zhengyan Wang; Penglai Li; Dongfang Qiu; Wentao Liu (Chemical Engineering Journal, 2025)

Evaluation of the effect of substrate structure on the passive soot oxidation and NOx reduction of DPF coated with SCO-SCR catalyst - Ying-Jie Chen; Pi-Qiang Tan; Xiao-Jie Wang; Yang Liu; Kuo Wang; Xiao-Mei Yang; Di-Ming Lou; Zhi-Yuan Hu (Process Safety and Environmental Protection, 2025)

PHB/PBAT blended melt-blown micro-nano fiber carbon source for efficient solid-phase denitrification: Insights into low-carbon treatment and enhanced mechanism - Hao Yuan; Liang Tang; Ziwei Yang; Xiang Pi; Jinxiang Zhao; Rongshen Luo; Ming Tang; Zuwen Liu; Zhendong Lei; Shiyang Li (Chemical Engineering Journal, 2025)

NtLYK5 negatively regulates drought resistance in tobacco through H2O2-mediated leaf stomatal opening and closing - Yonglu Xue; Qiwei Yu; Gang Chen; Zhenbao Luo; Kai Pi; Baolin Xie; Kaiping Wu; Chenhao Shi; Renxiang Liu (Plant Cell Reports, 2025)

Synthesis and antibacterial activities of quercetagetin derivatives - Yuhui Tang; Wei Liu; Kang Li; Yingxue Yang; Zhehao He; Jianguo Zeng; Pi Cheng (Natural Product Research, 2025)

Interleukin-33 Knockout Promotes High Mobility Group Box 1 Release from Astrocytes by Acetylation Mediated by P300/CBP-Associated Factor in Experimental Autoimmune Encephalomyelitis - Yifan Xiao; Liyan Hao; Xinyi Cao; Yibo Zhang; Qingqing Xu; Luyao Qin; Yixuan Zhang; Yangxingzi Wu; Hongyan Zhou; Mengjuan Wu; Mingshan Pi; Qi Xiong; et al. (Neuroscience Bulletin, 2025)

Leaching model of an expanding coastal dumpsite considering climate change - Yijie Wang; Xiaoqing Pi; Vinay Yadav; Abid Hussain; Qian Liu; Yao Wang; Yuliang Guo; Yan Zhang; Xunchang Fei (Waste Management, 2025)

Spermatogenesis and ultrastructure of the spermatozoa at three ploidy levels in the bivalve species, Corbicula fluminea - Jie Pi; Yangxin Tang; Ying Fu; Xu Wang; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Tissue and Cell, 2025)

Physiological functions of the transcription factor GmZAT10-1 gene involved in the salt stress adaptation in soybean - Tianlei Zhang; Li Yu; Yutin Chen; Yi Zeng; Boyi Pi; Xun Liu; Bingjun Yu (Plant Science, 2025)

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

Associations of welding-related metals and hypertension in male welders: Roles of cytokinesis-block micronucleus cytome assay parameters - Xiayun Dai; Fan Wang; Yonggang Liao; Na Tu; Xiaolei Fu; Wenjuan Fu; Yizhe Sun; Junpin Liu; Siyu Wan; Wenjun Yin; Wei Pi; Jiaojun Liang; et al. (Environmental Pollution, 2025)

Association between multiple metals mixture and diabetic retinopathy in older adults with diabetes mellitus: a cross-sectional study in China - Shuren Ding; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Zhiqiang Zhao; Qing Wei; Shurong Pi; Fubin Chen; Qian Gu; Baixiang Xiao; et al. (Environmental Geochemistry and Health, 2025)

Spotlight on the long-term effects of micro/nanoplastics exposure on Spirulina platensis: Algal cells, extracellular polymeric substances, and phycocyanin - Zhiheng Yue; Jiangjin Qian; Wenjing Li; Xiaodan Liu; Huang Dai; Xin Liu; Fuwei Pi; Jiahua Wang (Food Chemistry, 2025)

Role of Glucose Metabolism in the Effects of Serum Metals on Telomere Length: Findings in Chinese Diabetic Population - Shuren Ding; Qian Gu; Zhiqiang Zhao; Yirong Xie; Feng Wang; Jieyi Liu; Hongya Li; Heng Su; Qing Wei; Shurong Pi; Fubin Chen; Baixiang Xiao; et al. (Biological Trace Element Research, 2025)

Regulation of PPARγ in the development of early sheep embryos in vitro - Hengbin Yu; Chang Liu; Yue Zhang; Zhenghang Li; Wenhui Pi; Guangdong Hu (Theriogenology, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Seagrass influence on mitigating ocean acidification and warming impacts on tropical calcifying macroalgae - Khaerul Awaluddin; Anderson B. Mayfield; Kwee Siong Tew; Pi-Jen Liu (Marine Environmental Research, 2025)

Temperature drives reproductive activity in a rare trioecy population of Corbicula clams - Jie Pi; Yangxin Tang; Neil E. Coughlan; Linwei Liu; Xu Wang; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2025)

Airway exposure to lithium nickel manganese cobalt oxide particles induces alterations in lung microenvironment and potential kidney and liver damage in mice - Junyi Wang; Xin Fang; Ruirui Wu; Ziyu Liu; Gang Wang; Yuxin Hu; Huihui Wang; Jingbo Pi; Yuanyuan Xu (Toxicology, 2025)

Systematic preparation of animal-derived glycosaminoglycans: Research progress and industrial significance - Sinong Liu; Yanpeng Xiang; Chang Xu; Jingxin Sun; Yuzhen Pi; Jun-Hua Shao (Food Chemistry, 2025)

Rock Mass Behavior During High Pressure Grouting: An In-Situ Experimental Investigation - Lipeng Liu; Xiaogang Wang; Jin Pi; Ruilang Cao; Qingwei Duan; Qiang Zhang (Rock Mechanics and Rock Engineering, 2025)

Exploring the freshness biomarker and volatiles formation in stored pork by means of lipidomics and volatilomics - Yuping Zhang; Jingyu Li; Zixu Zeng; Xiangru Wei; Nigel P. Brunton; Yanqing Yang; Peng Gao; Jiangtao Xing; Pi Li; Fangjie Liu; Rui Liu; Qianqian Li; et al. (Food Research International, 2025)

The possibility of the computer simulation-assisted IDDSI framework for the development of thickened brown rice paste - Zexue Lin; Shuhan Liu; Dongling Qiao; Xiaowen Pi; Binjia Zhang (Food Chemistry, 2025)

Adulteration detection of multi-species vegetable oils in camellia oil using Raman spectroscopy: Comparison of chemometrics and deep learning methods - Jiahua Wang; Jiangjin Qian; Mengting Xu; Jianyu Ding; Zhiheng Yue; Yanpeng Zhang; Huang Dai; Xiaodan Liu; Fuwei Pi (Food Chemistry, 2025)

Interaction between NOx reduction and soot oxidation for selective catalytic oxidation-selective catalytic reduction catalyst coated on diesel particulate filter: An experimental and numerical study - Ying-Jie Chen; Pi-Qiang Tan; Yang Liu; Kuo Wang; Xiao-Jie Wang; Xiao-Mei Yang; Di-Ming Lou; Zhi-Yuan Hu; Wen-Ming Yang (Chemical Engineering Journal, 2025)

Seasonal and annual variations of sediment trapping and particulate organic carbon burial in Yellow River reservoirs - Christian Miguel Huarez Yarleque; Anping Shu; Shaoda Liu; Roberto Xavier Supe Tulcan; Ziru Zhang; Chengling Pi; Yulong Xiao; Fuyang Zhu (Science of The Total Environment, 2024)

The evolution and relationship of the Yellow Sea warm current and the Yellow Sea Cold Water Mass since the Mid-Holocene and possible ENSO influences - Zhong Pi; Fengming Chang; Qingyun Nan; Yikun Cui; Qinghe Liu; Jingjing Zhang; Hongliang Li; Jianfang Chen; Tiegang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Comprehensive geophysical, geotechnical, and geochemical assessments of an offshore landfill in Singapore - Zhibo Zhang; Ziwen Yuan; Lei Hu; Frederic Coulon; Huaxin Liu; Zhanbo Cheng; Shifan Wu; Qian Liu; Xiaoqing Pi; Wei Wu; Xunchang Fei (Journal of Hazardous Materials, 2024)

N-doped pitch assisted local interface micro-environment tailoring and microcrystalline regulation in carbon nanotube for efficient oxygen reduction reaction - Jian Li; Wenhao Chen; Xinxin Pi; ZhenJia Liu; Xiequn Song; Kezhi Yang; Yanhui Li (Fuel, 2024)

A lipidomic and volatilomic approach to map the lipid profile and related volatile compounds in roasted quail meat using circulating non-fried roast technology - Huan Liu; Yuping Zhang; Hengbin Ji; Junke Li; Qianli Ma; Nazimah Hamid; Jiangtao Xing; Peng Gao; Pi Li; Jianxun Li; Qianqian Li (Food Chemistry, 2024)

Degradation Of Tetracycline Antibiotic in Water by an Electro/Peroxydisulfate System Catalyzed with Fe2+ and Cu2+ Loaded on Activated Carbon - Nana Wu; Guangze Wu; Yuying Pi; Qiang Liu; Fuchen Ban; Yulan Tang; Yifei Wei (Water, Air, & Soil Pollution, 2024)

Silver nanoparticles exhibit ecotoxicological effects via oxidative stress, inflammation, and reproductive toxicity in Asian clam (Corbicula fluminea) - Chun Li; Zhiming Liu; Yang Xu; Jie Pi; Qiushi Zhang; Xiaoying Chen; Chengfeng Zhan; Liang Hu; Jibang Xie; Ziyu Xie; Xinlan Deng; Lixin Wen; et al. (Chemosphere, 2024)

Formation and retention of aroma compounds in pigeons roasted by circulating non-fried roast technique by means of UHPLC-HRMS and GC-O-MS - Huan Liu; Jingyu Li; Yuping Zhang; Lin Li; Hansheng Gong; Lixuan Tan; Peng Gao; Pi Li; Jiangtao Xing; Bin Liang; Jianxun Li (Food Chemistry, 2024)

Feasibility and Acceptability Evaluation of a Digital Therapeutic Program for Improving Cancer Prevention: A Quasi-experimental Pre-post Interventional Pilot Study - Xianwei Zhang; Sheng Zhang; Haiyan Zhang; Ziyou Xiong; Yi Li; Lufeng Li; Xitian Pi; Hongying Liu (Journal of Cancer Education, 2024)

Niche similarity accompanying COI genetic differentiations in asexual and sexual Corbicula lineages within East and Southeast Asia - Yangxin Tang; Jie Pi; Neil E. Coughlan; Linwei Liu; Xinhua Liu; Jianguo Xiang; Deliang Li (Hydrobiologia, 2024)

Cross-media transfer of polycyclic aromatic hydrocarbons in the Naples metropolitan area, southern Italy - Wen Pi; Chengkai Qu; Yang Ding; Xiaoshui Li; Ao Liu; Wenping Li; Benedetto De Vivo; Alberto Fortelli; Shihua Qi; Stefano Albanese (Science of The Total Environment, 2024)

WUSCHEL RELATED HOMEOBOX5 and 7 maintain callus development by promoting cell division in Arabidopsis - Yi Yang; Caifeng Liu; Yue Yu; Guiping Ran; Ning Zhai; Limin Pi (Plant Science, 2024)

Unraveling the formation mechanism of aroma compounds in pork during air frying using UHPLC-HRMS and Orbitrap Exploris GC–MS - Jingyu Li; Yuping Zhang; Renyu Zhang; Rujie Yang; Qianli Ma; Zhongshuai Wang; Pi Li; Jiangtao Xing; Peng Gao; Huan Liu; Hansheng Gong (Food Research International, 2024)

Maternal pre-pregnancy BMI influences the associations between bisphenol and phthalate exposures and maternal weight changes and fat accumulation - Nathalie Irvine; Rhonda C. Bell; Fatheema B. Subhan; Catherine J. Field; Jiaying Liu; Amy M. MacDonald; David W. Kinniburgh; Jonathan W. Martin; Deborah Dewey; Gillian England-Mason; B.J. Kaplan; C.J. Field; et al. (Environmental Research, 2024)

Experimental investigation of the roughness, freezing temperature and normal stress on the shear mechanical action of frozen saturated clay-rock interface - Haowei Cai; Shibing Huang; Yonglong Yang; Fei Liu; Zhijie Pi (Cold Regions Science and Technology, 2024)

Catalytic oxidation of SO2 in O2-aerated aqueous Solution: superior catalytic capability of KOH/urea-treated biochars and catalytic mechanism - Liu Pi; Yan Shao; Tao Xu; Junru Ma; Yan Li; Xuhui Mao (Chemical Engineering Journal, 2024)

Preliminary Investigation Into the Antidepressant Effects of a Novel Curcumin Analogue (CACN136) In Vitro and In Vivo - Jinglin Chen; Yumeng Wei; Nong Li; Chao Pi; Wenmei Zhao; Yueting Zhong; Wen Li; Hongping Shen; Yan Yang; Wenwu Zheng; Jun Jiang; Zerong Liu; et al. (Molecular Neurobiology, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Reducing microplastics in tea infusions released from filter bags by pre-washing method: Quantitative evidences based on Raman imaging and Py-GC/MS - Zhiheng Yue; Xiaodan Liu; Tingna Mei; Yanpeng Zhang; Fuwei Pi; Huang Dai; Yi Zhou; Jiahua Wang (Food Chemistry, 2024)

BIG coordinates auxin and SHORT ROOT to promote asymmetric stem cell divisions in Arabidopsis roots - Zhongming Liu; Pengyue Sun; Xuemei Li; Wen Xiao; Limin Pi; Yun-Kuan Liang (Plant Cell Reports, 2024)

Stem Cell Therapy in Neonatal Hypoxic-Ischemic Encephalopathy and Cerebral Palsy: a Bibliometric Analysis and New Strategy - Qiu-Xia Xiao; Min-Jian Geng; Yi-Fei Sun; Yu Pi; Liu-Lin Xiong (Molecular Neurobiology, 2024)

Exploring mycorrhizal diversity in sympatric mycoheterotrophic plants: a comparative study of Monotropastrum humile var. humile and M. humile var. glaberrimum - Ren-Cheng Liu; Wan-Rou Lin; Pi-Han Wang (Mycorrhiza, 2024)

Influence of gestational hypertension and maternal air pollutant exposure on birth outcomes - Tai-Ho Hung; Te-Yao Hsu; Jie Hsu; Chia-Yu Ou; Pi-Hua Liu; Liang-Ming Lo; Steven W Shaw; Gwo-Hwa Wan (Environmental Science and Pollution Research, 2024)

Interfacial solar evaporation driven Cd removal from contaminated sediments - Keyi Liu; Pan Wu; Yang Ye; Jiashu Jiang; Yuhao Guo; Yuejianshu Li; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2024)

Enhancing the electrochemical activation kinetics of V2O3 for high-performance aqueous zinc-ion battery cathode materials - Yuexin Liu; Chenlong Gao; Yuning Sun; Xuxia Hao; Zhengjie Pi; Menghao Yang; Xiaoli Zhao; Kefeng Cai (Chemical Engineering Journal, 2024)

Sesame allergy: mechanisms, prevalence, allergens, residue detection, effects of processing and cross-reactivity - Xiaowen Pi; Zeyu Peng; Jiafei Liu; Yunqing Jiang; Jiarong Wang; Guiming Fu; Yili Yang; Yuxue Sun (Critical Reviews in Food Science and Nutrition, 2024)

Structural evolution and the influence mechanism of the global embedded tungsten value flow networks: The perspective of value chain and technological progress - Nanfei Jia; Zhengrong Pi; Min Zuo; Donghui Liu; Haizhong An; Jialiang Wang (Resources Policy, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Non-destructive detection and grading of chilling injury-induced lignification of kiwifruit using X-ray computer tomography and machine learning - Jiahua Wang; Yuqing Lin; Qiaocong Li; Zelin Lu; Jiangjin Qian; Huang Dai; Fuwei Pi; Xiaodan Liu; Yong He (Computers and Electronics in Agriculture, 2024)

Characteristics of ash formed by different lubricant additives and its effect on DPF performance - Pi-qiang Tan; Tian-peng Liu; Li-shuang Duan; Yi-fan Yin; Di-ming Lou; Zhi-yuan Hu (Fuel, 2024)

Fe7C3 nanoparticles anchored on N-doped biochar as electrocatalyst for highly efficient oxygen evolution reaction - Wenhao Chen; Weitao Cao; Xinxin Pi; Zhen Liu; Zhiyang Li; Jian Li; Zhenyu Jing; Qiuju Du; Xiaoyong Lai; Yanhui Li (Fuel, 2024)

Transparent self-cleaning coatings repellent to ultralow surface tension liquids in extreme environments - Liying Liu; Min Zhang; Yuanyang Yan; Yahong Zhou; Shuangfeng Wang; Pihui Pi; Xiufang Wen; Yu Qian; Lei Jiang (Chemical Engineering Journal, 2024)

Solution chemistry strategies to construct a stable MAPbI3 film toward high performance of amplified spontaneous emission - Haoyue Luo; Mingyu Pi; Zijun Zhan; Nian Liu; Xin Zeng; Jie Zeng; Yuan Xiang; Xinyi Kuang; Yexiong Huang; Juan Du; Dingke Zhang; Zhengzheng Liu; et al. (Chemical Engineering Journal, 2024)

Progress on aptamer-based SERS sensors for food safety and quality assessment: methodology, current applications and future trends - Guoyong Jiang; Yu Li; Jinghan Liu; Ling Liu; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2024)

Mechanism of arsenic accumulation in sediments of the northern China: Insight from provenance, weathering processes and paleoenvironmental changes - Wenjing Liu; Xianjun Xie; Kunfu Pi; Yanxin Wang (Journal of Hydrology, 2024)

In situ Raman characterization of the stability of blueberry anthocyanins in aqueous solutions under perturbations in temperature, UV, pH - Chuchu Duan; Xiaofeng Xiao; Yonghui Yu; Mengting Xu; Yanpeng Zhang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Chemistry, 2024)

Exploring the formation and retention of aroma compounds in ready-to-eat roasted pork from four thermal methods: A lipidomics and heat transfer analysis - Huan Liu; Qianli Ma; Jiangtao Xing; Pi Li; Peng Gao; Nazimah Hamid; Zhongshuai Wang; Ping Wang; Hansheng Gong (Food Chemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

First report of stem canker on durian and jackfruit caused by Fusarium decemcellulare in Taiwan - Pi-Chuan Liu; Jia-Rong Tang (Journal of Plant Pathology, 2023)

A Numerical Study on Modeling Ship Maneuvering Performance Using Twin Azimuth Thrusters - Tunbiao Wu; Ronghui Li; Qinglong Chen; Guiyuan Pi; Shijie Wan; Qiao Liu (Journal of Marine Science and Engineering, 2023)
A methodology of mathematical testing is proposed for a ship with twin azimuth thrusters based on numerical calculations. An unmanned surface vessel (USV) powered by two azimuth thrusters is considered, which is a model-scale configuration. The Ship Maneuvering Mathematical Model Group (MMG) model is introduced to describe forces on the hull and propellers. A set of captive tests (planar motion mechanism (PMM) and open-water tests) were simulated using STAR-CCM+ (16.06.008-R8) software to obtain hull hydrodynamic derivatives and azimuth thruster hydrodynamic coefficients. A maneuvering test of the model-scale ship with two azimuth thrusters is built based on numerical results, and numerical results are compared with the model-scale experimental data to validate the feasibility of numerical methods. The findings show that the usability of the developed mathematical test in predicting the maneuvering ability of ships with two azimuth thrusters is confirmed through numerical calculations.

Photoredox catalysed reductive aminomethylation of quaternary benzophenanthridine alkaloids - Xinhao Wang; Lin Wang; Jingxuan Zhang; Yisong Liu; Hongqi Xie; Jianguo Zeng; Pi Cheng (Natural Product Research, 2023)

Understanding the role of lipids in aroma formation of circulating non-fried roasted chicken using UHPLC-HRMS-based lipidomics and heat transfer analysis - Huan Liu; Dengyong Liu; Raheel Suleman; Peng Gao; Pi Li; Jiangtao Xing; Qianli Ma; Nazimah Hamid; Ping Wang; Hansheng Gong (Food Research International, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Advances on removal of organophosphorus pesticides with electrochemical technology - Yuqi Wan; Jinghan Liu; Fuwei Pi; Jiahua Wang (Critical Reviews in Food Science and Nutrition, 2023)

Routine analysis of pesticides in foodstuffs: Emerging ambient ionization mass spectrometry as an alternative strategy to be on your radar - Jingkun Li; Jinghan Liu; Yuqi Wan; Jiahua Wang; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2023)

Gain-of-function allele of HPY1 coordinates source and sink to increase grain yield in rice - Fengfeng Fan; Manman Liu; Nannan Li; Yu Guo; Huanran Yuan; Fengfeng Si; Mingxing Cheng; Gaili Chen; Meng Cai; Nengwu Li; Yixin Zhang; Yi Yu; et al. (Science Bulletin, 2023)

Cotton-based bionic tree-shaped photothermal evaporator for extraction of heavy metals from river sediment - Keyi Liu; Yuejianshu Li; Pan Wu; Yuhao Guo; Yang Ye; Jiashu Jiang; Jiankai Hu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

Tetracycline hydrochloride degradation by activation of peroxymonosulfate with lanthanum copper Ruddlesden-Popper perovskite oxide: Performance and mechanism - Yitian Xia; Xiaoming Li; You Wu; Zhuo Chen; Zhoujie Pi; Abing Duan; Junwu Liu (Chemosphere, 2023)

Experimental study of emission characteristics and performance of SCR coated on DPF with different catalyst washcoat loadings - Pi-qiang Tan; Ying-jie Chen; Zi-tong Wang; Li-shuang Duan; Yang Liu; Di-ming Lou; Zhi-yuan Hu; Yun-hua Zhang (Fuel, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Research on the Potential Biomarkers of Mild Traumatic Brain Injury: a Systematic Review and Bibliometric Analysis - Yishu Liu; Chudong Wang; Zhiyun Pi; Tingting Wang; Changquan Zhang; Jifeng Cai (Molecular Neurobiology, 2023)

Organic ultraviolet filter mixture promotes bleaching of reef corals upon the threat of elevated seawater temperature - Tangtian He; Mirabelle M.P. Tsui; Anderson B. Mayfield; Pi-Jen Liu; Te-Hao Chen; Li-Hsueh Wang; Tung-Yung Fan; Paul K.S. Lam; Margaret B. Murphy (Science of The Total Environment, 2023)

Nanomaterials-modulated Fenton reactions: Strategies, chemodynamic therapy and future trends - Junjie Qi; Guoyong Jiang; Yuqi Wan; Jinghan Liu; Fuwei Pi (Chemical Engineering Journal, 2023)

Pick-up of fluoroquinolones from the aqueous phase via magnetically propeled microrobots: kinetics, thermodynamics, and site energy distribution analysis - Yongzheng Tang; Wenpeng Jia; Mutai Bao; Shengyao Qiu; YongRui Pi; Chongfeng Liu; Jinchen Zhao (Frontiers in Marine Science, 2023)
Removing fluoroquinolones (FQs) in marine culture tailwater is crucial for the coastal marine environment. The application of a bacteria-based microrobot for FQ removal was discussed. Norfloxacin (NOR) and levofloxacin (LEV) had static maximum adsorption capacities of 114.8 and 49.4 mg/g, respectively, by a magnetic microrobot. The experimental results of NOR adsorption by a magnetic microrobot were well supported by the Langmuir isotherm and Elovich kinetic models. Both the Langmuir isotherm model and the pseudo-second-order kinetic model may be able to accurately represent the LEV adsorption process. The mass transfer mechanism of the NOR and LEV adsorptions was divided into two steps and described better using the intraparticle diffusion (IPD) model. The exothermic and spontaneity of the sorption process were demonstrated through the study of thermodynamics. The magnetic microrobot’s heterogeneous surface was validated by the examination of site energy distribution. Additionally, this study demonstrated that the majority of the NOR and LEV sorption took place at sites with energies over 4.25 and 17.36 kJ/mol, respectively, supporting the notion that NOR and LEV adsorption constitute physical–chemical processes. Based on the above results, a magnetic microrobot, as a new-style green bio-adsorbent, can potentially be used to remove NOR and LEV from the mariculture in an inexpensive and effective manner.

Elevated serum lead and cadmium levels associated with increased risk of dyslipidemia in children aged 6 to 9 years in Shenzhen, China - Shufan Li; Ruiguo Liu; Yueyang Wu; Rimei Liang; Zhijiang Zhou; Jiaqi Chen; Yingbin You; Pi Guo; Qingying Zhang (Environmental Science and Pollution Research, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Sulfide causes histological damage, oxidative stress, metabolic disorders and gut microbiota dysbiosis in juvenile sea cucumber Apostichopus japonicus Selenka - Ye Zhao; Han Wang; Haona Wang; Hui Liu; Yanying Zhang; Jianwei Zhang; Yongrui Pi; Pei Yang; Qing Wang (Aquatic Toxicology, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Boosting the selectivity of higher alcohols in upgrading of aqueous bioethanol over amphiphilic NiSn@C-MgO catalyst - Xueying Cai; Xiyin Li; Minyang Dang; Huanxin Huang; Ailin Liu; Qian Zhang; Yunhong Pi; Qingwei Meng; Xiaoping Wu; Tiejun Wang (Fuel, 2023)

Effect of a novel catalyst zonal coating strategy on the performance of SCR coated particulate filters - Pi-qiang Tan; Li-shuang Duan; Yang Liu; Ying-jie Chen; Di-ming Lou; Zhi-yuan Hu (Fuel, 2023)

Heat-induced changes in epitopes and IgE binding capacity of soybean protein isolate - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Protein modification, IgE binding capacity, and functional properties of soybean protein upon conjugation with polyphenols - Xiaowen Pi; Jiafei Liu; Yuxue Sun; Qingfeng Ban; Jianjun Cheng; Mingruo Guo (Food Chemistry, 2023)

Fabrication of foxtail millet prolamin/caseinate/chitosan hydrochloride composite nanoparticles using antisolvent and pH-driven methods for curcumin delivery - Xiao Chen; Yan-Chao Wu; Liu-Hong Qian; Yu-He Zhang; Pi-Xian Gong; Wei Liu; Hui-Jing Li (Food Chemistry, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

Electric field-enhanced immobilization of Cd and Pb in contaminated river sediments - Shan Gao; Xiong Yang; Yucheng Ding; Yihui Xia; Yumiao Song; Jiaying Liu; Kewu Pi; Andrea R. Gerson (Chemosphere, 2023)

Mechanisms of changing speciation and bioavailability of selenium in agricultural mollisols of northern cold regions - Li Zhang; Junna Ning; Guodong Liu; Lei Tong; Yiqun Gan; Chenglu Li; Wenpeng Yang; Kunfu Pi (Science of The Total Environment, 2023)

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

Phytosterol of lotus seed core powder alleviates hypercholesterolemia by regulating gut microbiota in high-cholesterol diet-induced C57BL/6J mice - Dongmin Liu; Jiating Pi; Bo Zhang; Hongliang Zeng; Changzhu Li; Zhihong Xiao; Fang Fang; Miao Liu; Na Deng; Jianhui Wang (Food Bioscience, 2023)

The role of PIWI-interacting RNA in naringin pro-angiogenesis by targeting HUVECs - Yixing Pi; Zitian Liang; Qianzhou Jiang; Ding Chen; Zhikang Su; Yuanting Ouyang; Zhiyi Zhang; Jiaohong Liu; Siyi Wen; Li Yang; Tao Luo; Lvhua Guo (Chemico-Biological Interactions, 2023)

Characterization of the improved functionality in soybean protein-proanthocyanidins conjugates prepared by the alkali treatment - Xiaowen Pi; Yuxue Sun; Jiafei Liu; Xu Wang; Weichen Hong; Jianjun Cheng; Mingruo Guo (Food Hydrocolloids, 2023)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Numerical Simulation on Dynamic Characteristics of Longitudinal Launching of Large Container Ships - Kaihua Liu; Yu Wang; Zhifei Wu; Juntao Pi; Wie Min Gho; Bo Zhou (Journal of Marine Science and Engineering, 2022)
The upsizing and rapid development of container ships has resulted in many large ships launching in small slipways due to the lagging of advanced equipment. In particular, the dynamic characteristics of these large ships in the longitudinal launching operation under restricted water are yet to be studied in detail. In this study, a ship model to simulate the longitudinal launching process of an 8500 TEU container ship was created based on the URANS method. The ship resistance in calm water was determined and validated against the experimental data. The influence of the stern appendage on the ship’s resistance and the flow field around the hull, with and without the aft poppet, under various water-depth-to-draught ratios was analyzed. A comparison of the ship’s resistance between the numerical and the experimental data shows that the difference is minimal, within 1.5%. The numerical results revealed that the aft poppets change the flow pattern and effectively reduce the pressure drag in the drifting stage. The shallow water causes a restraining effect on the ship. The proposed analytical approach in the numerical analysis, considering the aft poppet and the water depth, could provide a better simulation for a large ship’s longitudinal launching operation.

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

The role of Th17 cells: explanation of relationship between periodontitis and COPD? - Jiaohong Liu; Yuanting Ouyang; Zhiyi Zhang; Siyi Wen; Yixing Pi; Ding Chen; Zhikang Su; Zitian Liang; Lvhua Guo; Yan Wang (Inflammation Research, 2022)

Zirconium-modified biochar as the efficient adsorbent for low-concentration phosphate: performance and mechanism - Qi Huang; Kun Luo; Zhoujie Pi; Li He; Fubing Yao; Shengjie Chen; Kunjie Hou; Yujie Liu; Xiaoming Li; Qi Yang (Environmental Science and Pollution Research, 2022)

Natural medicine combined with nanobased topical delivery systems: a new strategy to treat psoriasis - Zhiyue Zhao; Tao Liu; Shan Zhu; Jiaxin Pi; Pan Guo; Dongli Qi; Zhidong Liu; Nan Li (Drug Delivery and Translational Research, 2022)

Assessing the Effects of Ocean Warming and Acidification on the Seagrass Thalassia hemprichii - Pi-Jen Liu; Hong-Fong Chang; Anderson B. Mayfield; Hsing-Juh Lin (Journal of Marine Science and Engineering, 2022)
Seagrass beds serve as important carbon sinks, and it is thought that increasing the quantity and quality of such sinks could help to slow the rate of global climate change. Therefore, it will be important to (1) gain a better understanding of seagrass bed metabolism and (2) document how these high-productivity ecosystems are impacted by climate change-associated factors, such as ocean acidification (OA) and ocean warming (OW). A mesocosm-based approach was taken herein in which a tropical, Western Pacific seagrass species Thalassia hemprichii was cultured under either control or OA-simulating conditions; the temperature was gradually increased from 25 to 31 °C for both CO2 enrichment treatments, and it was hypothesized that this species would respond positively to OA and elevated temperature. After 12 weeks of exposure, OA (~1200 ppm) led to (1) increases in underground biomass and root C:N ratios and (2) decreases in root nitrogen content. Rising temperatures (25 to 31 °C) increased the maximum quantum yield of photosystem II (Fv:Fm), productivity, leaf growth rate, decomposition rate, and carbon sequestration, but decreased the rate of shoot density increase and the carbon content of the leaves; this indicates that warming alone does not increase the short-term carbon sink capacity of this seagrass species. Under high CO2 and the highest temperature employed (31 °C), this seagrass demonstrated its highest productivity, Fv:Fm, leaf growth rate, and carbon sequestration. Collectively, then, it appears that high CO2 levels offset the negative effects of high temperature on this seagrass species. Whether this pattern is maintained at temperatures that actually induce marked seagrass stress (likely beginning at 33–34 °C in Southern Taiwan) should be the focus of future research.

Adaptability of organic matter and solid content to Fe2+/persulfate and skeleton builder conditioner for waste activated sludge dewatering - Xiaoran Li; Yafei Shi; Xi Zhou; Lu Wang; Huiqin Zhang; Kewu Pi; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2022)

Antibiotics Alter Pocillopora Coral-Symbiodiniaceae-Bacteria Interactions and Cause Microbial Dysbiosis During Heat Stress - Michael T. Connelly; Crystal J. McRae; Pi-Jen Liu; Cecily E. Martin; Nikki Traylor-Knowles (Frontiers in Marine Science, 2022)
Symbioses between eukaryotes and their associated microbial communities are fundamental processes that affect organisms’ ecology and evolution. A unique example of this is reef-building corals that maintain symbiotic associations with dinoflagellate algae (Symbiodiniaceae) and bacteria that affect coral health through various mechanisms. However, little is understood about how coral-associated bacteria communities affect holobiont heat tolerance. In this study, we investigated these interactions in four Pocillopora coral colonies belonging to three cryptic species by subjecting fragments to treatments with antibiotics intended to suppress the normal bacteria community, followed by acute heat stress. Separate treatments with only antibiotics or heat stress were conducted to compare the effects of individual stressors on holobiont transcriptome responses and microbiome shifts. Across all Pocillopora species examined, combined antibiotics and heat stress treatment significantly altered coral-associated bacteria communities and caused major changes in both coral and Cladocopium algal symbiont gene expression. Individually, heat stress impaired Pocillopora protein translation and activated DNA repair processes, while antibiotics treatments caused downregulation of Pocillopora amino acid and inorganic ion transport and metabolism genes and Cladocopium photosynthesis genes. Combined antibiotics-heat stress treatments caused synergistic effects on Pocillopora and Cladocopium gene expression including enhanced expression of oxidative stress response genes, programed cell death pathways and proteolytic enzymes that indicate an exacerbated response to heat stress following bacteria community suppression. Collectively, these results provide further evidence that corals and their Symbiodiniaceae and bacteria communities engage in highly coordinated metabolic interactions that are crucial for coral holobiont health, homeostasis, and heat tolerance.

Biomimetic synthesis of 6-substituted dihydrobenzophenanthridine alkaloids based on visible-light promoted radical addition reaction - Pi Cheng; Wei Wang; Xinhao Wang; Lin Wang; Wei Liu; Jianguo Zeng (Natural Product Research, 2022)

Vaccination with virus-like particles of atypical porcine pestivirus inhibits virus replication in tissues of BALB/c mice - Jianxin Liu; Pengtao Zhang; Yongjie Chen; Wenxia Zhong; Baojian Li; Molin Pi; Zhangyong Ning (Archives of Virology, 2021)

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Sensitive Techniques for POCT Sensing on the Residues of Pesticides and Veterinary Drugs in Food - Lin Liu; Yueying Gao; Jinghan Liu; Ying Li; Ziye Yin; Yuanyuan Zhang; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Current Progress on Antibiotic Sensing Based on Ratiometric Fluorescent Sensors - Jinghan Liu; Ying Li; Lin Liu; Yueying Gao; Yuanyuan Zhang; Ziye Yin; Fuwei Pi; Xiulan Sun (Bulletin of Environmental Contamination and Toxicology, 2021)

Impacts of Seagrass on Benthic Microalgae and Phytoplankton Communities in an Experimentally Warmed Coral Reef Mesocosm - Kwee Siong Tew; Jimmy Kuo; Jing-O Cheng; Fung-Chi Ko; Pei-Jie Meng; Anderson B. Mayfield; Pi-Jen Liu (Frontiers in Marine Science, 2021)
The effects of seagrass on microalgal assemblages under experimentally elevated temperatures (28°C) and CO 2 partial pressures (pCO 2 ; 800 μatm) were examined using coral reef mesocosms. Concentrations of nitrate, ammonium, and benthic microalgal chlorophyll a (chl-a) were significantly higher in seagrass mesocosms, whereas phytoplankton chl-a concentrations were similar between seagrass and seagrass-free control mesocosms. In the seagrass group, fewer parasitic dinoflagellate OTUs (e.g., Syndiniales) were found in the benthic microalgal community though more symbiotic dinoflagellates (e.g., Cladocopium spp.) were quantified in the phytoplankton community. Our results suggest that, under ocean acidification conditions, the presence of seagrass nearby coral reefs may (1) enhance benthic primary productivity, (2) decrease parasitic dinoflagellate abundance, and (3) possibly increase the presence of symbiotic dinoflagellates.

Nrf2 deficiency aggravates the kidney injury induced by subacute cadmium exposure in mice - Chengjie Chen; Xue Han; Gang Wang; Dan Liu; Lina Bao; Congcong Jiao; Junjun Luan; Yongyong Hou; Yuanyuan Xu; Huihui Wang; Qiang Zhang; Hua Zhou; et al. (Archives of Toxicology, 2021)

Genome-wide analysis of chloride channel-encoding gene family members and identification of CLC genes that respond to Cl−/salt stress in upland cotton - Xun Liu; Boyi Pi; Jianwei Pu; Cong Cheng; Jiajia Fang; Bingjun Yu (Molecular Biology Reports, 2020)

Biogeographical distribution of dissimilatory nitrate reduction to ammonium (DNRA) bacteria in wetland ecosystems around the world - Huawei Pan; Dongdan Yuan; Weiyue Liu; Yanxia Pi; Shanyun Wang; Guibing Zhu (Journal of Soils and Sediments, 2020)

Enhanced dewater efficiency for river sediment by top-to-bottom water transmitting channels with different materials - Zhuo Shi; Kewu Pi; Xuanming Huang; Yafei Shi; Ziwen Chen; Ruyu Tang; Zehui Hu; Andrea R. Gerson; Defu Liu (Environmental Science and Pollution Research, 2020)

The Behavior of Cadmium Leaching from Contaminated Soil by Nitrilotriacetic Acid: Implication for Cd-Contaminated Soil Remediation - Xianjun Xie; Sen Yang; Hongxing Liu; Kunfu Pi; Yanxin Wang (Water, Air, & Soil Pollution, 2020)

Contrasting Changes in Diel Variations of Net Community Calcification Support That Carbonate Dissolution Can Be More Sensitive to Ocean Acidification Than Coral Calcification - Wen-Chen Chou; Pi-Jen Liu; Ying-Hsuan Chen; Wei-Jen Huang (Frontiers in Marine Science, 2020)

The effects of El Niño‐Southern Oscillation events on intertidal seagrass beds over a long‐term timescale - Hsing‐Juh Lin; Chen‐Lu Lee; Shang‐En Peng; Meng‐Chi Hung; Pi‐Jen Liu; Anderson B. Mayfield (Global Change Biology, 2018)
El Niño‐Southern Oscillation (ENSO) events can cause dramatic changes in marine communities. However, we know little as to how ENSO events affect tropical seagrass beds over decadal timescales. Therefore, a diverse array of seagrass ( Thalassia hemprichii ) habitat types were surveyed once every 3 months for 16 years (January 2001 to February 2017) in a tropical intertidal zone that is regularly affected by both ENSO events and anthropogenic nutrient enrichment. La Niña and El Niño events had distinct effects on the biomass and growth of T. hemprichii . During La Niña years, higher (a) precipitation levels and (b) seawater nitrogen concentrations led to increases in seagrass leaf productivity, canopy height, and biomass. However, the latter simultaneously stimulated the growth of periphyton on seagrass leaves; this led to decreases in seagrass cover and shoot density. More frequent La Niña events could, then, eventually lead to either a decline in intertidal seagrass beds or a shift to another, less drought‐resistant seagrass species in those regions already characterized by eutrophication due to local anthropogenic activity.

Effects of long-term fertilization practices on heavy metal cadmium accumulation in the surface soil and rice plants of double-cropping rice system in Southern China - Yilan Xu; Haiming Tang; Tangxing Liu; Yifeng Li; Xinjie Huang; Jun Pi (Environmental Science and Pollution Research, 2018)

Effect of water salinity and rock components on wettability alteration during low-salinity water flooding in carbonate rocks - Wenbo Su; Yuetian Liu; Jian Pi; Rukuan Chai; Changyong Li; Yunpeng Wang (Arabian Journal of Geosciences, 2018)

Effects of Cadmium Exposure on Metal Accumulation and Energy Metabolism of Silver Carp (Hypophthalmichthys molitrix) - Deliang Li; Jie Pi; Jianping Wang; Pengfei Zhu; Deming Liu; Ting Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

The phosphodiesterase-4 inhibitor roflumilast decreases ethanol consumption in C57BL/6J mice - Xin Liu; Pi-Da Hao; Ming-Feng Yang; Jing-Yi Sun; Lei-Lei Mao; Cun-Dong Fan; Zong-Yong Zhang; Da-Wei Li; Xiao-Yi Yang; Bao-Liang Sun; Han-Ting Zhang (Psychopharmacology, 2017)

Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata - Zhi-Xing Qing; Peng Yang; Kun Yu; Xue-Yi Yang; Jing-Hong Liu; Feng Xiang; Hua-Liang Cao; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2017)

Response of Selenium and Selenogenome in Immune Tissues to LPS-Induced Inflammatory Reactions in Pigs - Lv-Hui Sun; Ding-An Pi; Ling Zhao; Xiu-Ying Wang; Luo-Yi Zhu; De-Sheng Qi; Yu-Lan Liu (Biological Trace Element Research, 2017)

Spatiotemporal evolution and driving forces of changes in rural settlements in the poverty belt around Beijing and Tianjin: a case study of Zhangjiakou city, Hebei Province - Pi-ling Sun; Yue-qing Xu; Qing-guo Liu; Chao Liu; Hong-liang Wang (Journal of Mountain Science, 2017)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

TRPV1 attenuates intracranial arteriole remodeling through inhibiting VSMC phenotypic modulation in hypertension - Ming-Jie Zhang; Yun Liu; Zi-Cheng Hu; Yi Zhou; Yan Pi; Lu Guo; Xu Wang; Xue Chen; Jing-Cheng Li; Li-Li Zhang (Histochemistry and Cell Biology, 2017)

Effect of pH on the adsorption and photocatalytic degradation of sulfadimidine in Vis/g-C3N4 progress - Bin Yang; Xuhui Mao; Liu Pi; Yixiao Wu; Huijun Ding; Weihao Zhang (Environmental Science and Pollution Research, 2017)

Low-cost magnetic herbal biochar: characterization and application for antibiotic removal - Xiangrui Kong; Yaoxuan Liu; Jiachang Pi; Wenhong Li; QianJiahua Liao; Jingge Shang (Environmental Science and Pollution Research, 2017)

Synthesis and biological evaluation of n-butylphthalide derivatives as anti-platelet aggregation agents - Meihui Chen; Qi Liu; Min Tan; Shijun Wen; Rongbiao Pi; Dingkun Lin (Natural Product Research, 2016)

Protective Effects of Calcium on Cadmium Accumulation in Co-Cultured Silver Carp (Hypophthalmichthys molitrix) and Triangle Sail Mussel (Hyriopsis cumingii) - Deliang Li; Jie Pi; Jianping Wang; Pengfei Zhu; Liuping Lei; Ting Zhang; Deming Liu (Bulletin of Environmental Contamination and Toxicology, 2016)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Abrp, a new gene, confers reduced susceptibility to tetracycline, glycylcine, chloramphenicol and fosfomycin classes in Acinetobacter baumannii - X. Li; J. Quan; Y. Yang; J. Ji; L. Liu; Y. Fu; X. Hua; Y. Chen; B. Pi; Y. Jiang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite O dontotermes formosanus - Hongjie Li; Carsten Dietrich; Na Zhu; Aram Mikaelyan; Bin Ma; Ruoxi Pi; Yu Liu; Mengyi Yang; Andreas Brune; Jianchu Mo (Environmental Microbiology, 2016)
Summary Fungus‐cultivating termites ( M acrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose‐degrading fungal symbiont (genus T ermitomyces ), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of O dontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the bacterial communities colonizing specific microhabitats. Our results document strong differences between the communities at the hindgut epithelium and the luminal fluid of newly moulted, young and old worker termites. The differences in community structure were consistent with the density, morphology and spatial distribution of bacterial cells and the pools of microbial metabolites in the hindgut compartment, underlining that both gut development and the age‐specific changes in diet affect the composition and functional role of their gut microbiota. These findings provide strong support for the concept that changes in diet and gut environment are important determinants of community structure because they create new niches for microbial symbionts.

Rhizobia-inoculation enhances the soybean’s tolerance to salt stress - Liqun Qu; Yingying Huang; Chengmin Zhu; Houqing Zeng; Chenjia Shen; Cong Liu; Ying Zhao; Erxu Pi (Plant and Soil, 2016)

Association of polygalacturonase-inhibiting protein gene 2 (MsPGIP2) to common leaf spot resistance in alfalfa - Zhi Gui; Jianming Gao; Nan Xin; Yu Wang; Yongshuo Pi; Huiqin Liu; Qinghua Yuan; Xianglin Li (European Journal of Plant Pathology, 2016)

Assessment of ichthyotoxicity and anthropogenic contamination in the surface waters of Kenting National Park, Taiwan - Te-Hao Chen; Yi-Ling Chen; Chia-Yang Chen; Pi-Jen Liu; Jing-O Cheng; Fung-Chi Ko (Environmental Monitoring and Assessment, 2015)

Deep sequencing identifies conserved and novel microRNAs from antlers cartilage of Chinese red deer (Cervus elaphus) - Yanxia Chen; Xuedong Liu; Xiaoguang Yang; Yuhui Liu; Xiaomeng Pi; Qingzhen Liu; Dong Zheng (Genes & Genomics, 2015)

Numerical simulation and inversion of offshore area depth based on x-band microwave radar - Li Wang; Xiongbin Wu; Xiaoshan Pi; Ketao Ma; Jianfei Liu; Yun Tian (Acta Oceanologica Sinica, 2015)

Berberine protects homocysteic acid-induced HT-22 cell death: involvement of Akt pathway - Meihui Chen; Min Tan; Minghua Jing; Anmin Liu; Qinyu Liu; Shijun Wen; Ziwei Chen; Xiaojuan Chao; Xixin He; Charles Ramassamy; Youheng Gao; Rongbiao Pi (Metabolic Brain Disease, 2015)

Effects of elevated CO2 and temperature on the growth, elemental composition, and cell size of two marine diatoms: potential implications of global climate change - Kwee Siong Tew; Yu-Chen Kao; Fung-Chi Ko; Jimmy Kuo; Pei-Jie Meng; Pi-Jen Liu; David C. Glover (Hydrobiologia, 2014)

23,24-Dihydrocucurbitacin C: a new compound regarded as the next metabolite of cucurbitacin C - Zhi-Xing Qing; Yuan Zhou; Xiu-Bin Liu; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2014)

Facile synthesis of tetrahydroprotoberberine and protoberberine alkaloids from protopines and study on their antibacterial activities - Pi Cheng; Bin Wang; Xiubin Liu; Wei Liu; Weisong Kang; Jie Zhou; Jianguo Zeng (Natural Product Research, 2014)

Erratum to: Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Genetic variation in the carbonyl reductase 3 gene confers risk of type 2 diabetes and insulin resistance: a potential regulator of adipogenesis - Yi-Cheng Chang; Pi-Hua Liu; Yun-Chih Tsai; Yen-Feng Chiu; Shyang-Rong Shih; Low-Tone Ho; Wen-Jane Lee; Chieh-Hua Lu; Thomas Quertermous; J. David Curb; Wei-Jei Lee; Po-Chu Lee; et al. (Journal of Molecular Medicine, 2012)

Polysaccharides purified from the submerged culture of Ganoderma formosanum stimulate macrophage activation and protect mice against Listeria monocytogenes infection - Cheng-Li Wang; Chia-Chen Pi; Chu-Wei Kuo; Yu-Jing Zhuang; Kay-Hooi Khoo; Wen-Hsiung Liu; Chun-Jen Chen (Biotechnology Letters, 2011)

Temperature and pH controls on glycerol dibiphytanyl glycerol tetraether lipid composition in the hyperthermophilic crenarchaeon Acidilobus sulfurireducens - Eric S. Boyd; Ann Pearson; Yundan Pi; Wen-Jun Li; Yi Ge Zhang; Liu He; Chuanlun L. Zhang; Gill G. Geesey (Extremophiles, 2011)

An intelligent electronic capsule system for automated detection of gastrointestinal bleeding - Hong-ying Liu; Gang Wang; Kang Wei; Xi-tian Pi; Lan Zhu; Xiao-lin Zheng; Zhi-yu Wen (Journal of Zhejiang University-SCIENCE B, 2010)

Preliminary proteomic analysis of circulating polymorphonuclear neutrophils from rabbits experiencing scald injury and Staphylococcus aureus sepsis - Pi-hong Zhang; Li-li Li; Ji-zhang Zeng; Liu-rong Yang; Li-cheng Ren; Peng-fei Liang; Xiao-Yuan Huang (Inflammation Research, 2010)

Identification of a novel M-superfamily conotoxin with the ability to enhance tetrodotoxin sensitive sodium currents - Lei Wang; Junliang Liu; Canhui Pi; Xiayun Zeng; Maojun Zhou; Xiaoyu Jiang; Shangwu Chen; Zhenghua Ren; Anlong Xu (Archives of Toxicology, 2009)

Rates of overgrowth by macroalgae and attack by sea anemones are greater for live coral than dead coral under conditions of nutrient enrichment - Pi-Jen Liu; Shiue-Ming Lin; Tung-Yung Fan; Pei-Jie Meng; Kwang-Tsao Shao; Hsing-Juh Lina (Limnology and Oceanography, 2009)
A mesocosm experiment was conducted to determine the effects of nutrient enrichment on competitive interactions between a hard coral, a green alga, and a sea anemone. In the low‐nutrient controls, abundances of the green alga, Codium edule , and a sea anemone, Mesactinia genesis , remained low, and they coexisted with the live or dead scleractinian coral, Acropora muricata . Combined nitrogen and phosphorus additions markedly increased the photosynthetic efficiencies of zooxanthellae in A. muricata , the coverage of C. edule , and the asexual reproduction by M. genesis . After 35 d of nutrient addition, C. edule had begun to overgrow live A. muricata , but not dead coral. A. muricata finally died after 105 d, after being totally overgrown by C. edule. Within a few days of contact with live A. muricata , M. genesis was observed for the first time to have induced inflation of modified marginal aggressive organs known as acrorhagi tentacles, which it uses to attack neighboring coral. Nevertheless, M. genesis was not observed to attack C. edule , but moved away from it in the nutrient‐enriched tanks. The hierarchy of competitive superiority under nutrient enrichment was in the order of C. edule > M. genesis > A. muricata . From this experiment, it was evident that nutrient enrichment inhibits corals' ability to compete with sea anemones and algae in Nanwan Bay, southern Taiwan.

Molecular cloning and characterization of the promoter for the multiple stress-inducible gene BjCHI1 from Brassica juncea - Xue-Feng Wu; Chun-Lian Wang; En-Bei Xie; Ying Gao; Ying-Lun Fan; Pi-Qing Liu; Kai-Jun Zhao (Planta, 2009)

Development of a molecular marker for specific detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Jing-Yi Chang; En-Tzu Liu; Chih-Ping Chao; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2009)

Cryptotanshinone protects primary rat cortical neurons from glutamate-induced neurotoxicity via the activation of the phosphatidylinositol 3-kinase/Akt signaling pathway - Fangyan Zhang; Wenhua Zheng; Rongbiao Pi; Zhengrong Mei; Yingxia Bao; Jie Gao; Wenjie Tang; Shaorui Chen; Peiqing Liu (Experimental Brain Research, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)

Applications of ICA for the enhancement and classification of polarimetric SAR images - H. Wang; Y. Pi; G. Liu; H. Chen (International Journal of Remote Sensing, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Detrital flows through the feeding pathway of the oyster ( Crassostrea gigas ) in a tropical shallow lagoon: δ 13 C signals - Hwey-Lian Hsieh; Wen-Yuan Kao; Chang-Po Chen; Pi-Jen Liu (Marine Biology, 2000)